Infrastructure & Ops Hour DevSecOps with Patrick Debois - Newman, Sam; Dubois, Patrick (O'Reilly Media, Inc., 2021)
Join us for a special conversation on Kubernetes with Sam Newman and longtime DevOps pro Patrick Debois. They'll discuss DevSecOps best practices, how to develop a security-focused approach to your organization's software development, and the trends that are impacting your organization's deployment practices and culture-along with insights intended to help you learn how to approach the most challenging aspects of building and managing evolving software needs. What you'll learn-and how you can apply it Explore the origins of DevSecOps Understand why DevSecOps is needed See what's coming next for infrastructure and ops This training course is for you because ... You want the chance to ask Sam Newman and Patrick Debois your questions about using DevSecOps. You're looking for ways to use DevSecOps to support your production goals. You want to become well versed in the foundations and best practices of pipeline creation and deployment. Prerequisites Have a pen and paper handy to capture notes, insights, and inspiration Recommended follow-up: Read DevOpsSec (report) Watch Spotlight on Cloud: DevSecOps Lessons Learned with Zane Lackey (video, 58m) Read Securing DevOps (book) Watch " Security Is Everybody's Job " (recorded Superstream session with Tanya Janca) Read " Welcome to the Agile Revolution " (chapter 3 in Agile Application Security)
Online resource; Title from title screen (viewed May 5, 2021)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos